Finiteness properties for subgroups of GL(n, Z) - Bridson, M (2000)
We construct finitely presented subgroups of GL(n, ℤ) that have infinitely many conjugacy classes of finite subgroups. This answers a question of Grunewald and Platonov. We suggest a variation on their question.